GROWTH RESPONSE AND DROUGHT TOLERANCE OF THREE ECHINACEA PURPUREA ACCESSIONS AT DIFFERENT WATERING INTERVALS - Rina Puji Lestari; Ahmad Yunus; Samanhudi (Universitas Veteran Bangun Nusantara, 2026)
Drought is widely recognized as one of the most critical environmental constraints limiting plant growth and development, particularly in medicinal species such as Echinacea purpurea. This research was conducted to assess the growth performance and drought tolerance of three E. purpurea accessions exposed to different watering regimes. The study employed a completely randomized design arranged factorially, consisting of two experimental factors, namely accession (three accessions) and watering interval (1, 3, 5, and 7 days), with each treatment replicated five times. Statistical analysis was performed using analysis of variance (ANOVA), and significant differences among treatments were further evaluated using Duncan’s Multiple Range Test (DMRT) at the 5% probability level. The findings revealed that watering interval had a significant influence on plant growth, while the effect of accession was less pronounced for most observed variables. Daily watering resulted in superior growth performance, as reflected by greater plant height and a higher number of leaves. In contrast, extending the watering interval led to a marked reduction in growth. Among the evaluated accessions, accession 3 consistently exhibited better adaptation under limited water availability. Furthermore, differences in root-to-shoot ratio under drought conditions suggest the occurrence of adaptive mechanisms that enable plants to cope with water deficit stress. Overall, the results indicate that watering interval plays a more decisive role than accession in determining the growth of E. purpurea, whereas accession 3 possesses the greatest potential for drought tolerance. Keywords: drought stress, Echinacea purpurea, growth, drought tolerance